Risk perception and communication factors in aviation: Insights from safety investigators. Issue 7 (1st August 2022) - Chionis, Dimitrios; Karanikas, Nektarios; Iordan, Alice-Rebecca; Svensson-Dianellou, Antonia
Abstract: Although effective risk management is highly dependent on risk perception and communication, limited attention has been given to the influence and consideration of these two constructs and their factors in the aviation industry. This research aimed to map practices and perspectives of safety investigators regarding risk perception and communication in aviation and reveal respective influential parameters. The interviews with ten experienced safety investigators revealed that they consider and search risk perception and communication factors but with a divergent emphasis. Investigators acknowledged the effects of emotional and cognitive biases as well as the role of context when examining risk perception and communication factors and attributed the shaping of the latter to organisational practices, mainly training, supervisory and cultural aspects. Overall, the findings of this study suggest investigation methods could be enriched with a systematic approach to examining the role of risk perception and communication and considering their shaping factors while also providing directions for abating subjectivity when addressing these two constructs. This could be facilitated by developing a common reference framework for risk perception and communication and be accompanied by support from specialists and training in the management of investigators' heuristics.